EAU Guidelines on Urethral Trauma - (:unkn) unknown (ELSEVIER SCIENCE BV, 2010)
Context: These guidelines were prepared on behalf of the European Association of Urology (EAU) to assist urologists in the management of traumatic urethral injuries. Objective: To determine the optimal evaluation and management of urethral injuries by review of the world's literature on the subject. Evidence acquisition: A working group of experts on Urological Trauma was convened to review and summarize the literature concerning the diagnosis and treatment of genitourinary trauma, including urethral trauma. The Urological Trauma guidelines have been based on a review of the literature identified using on-line searches of MEDLINE and other source documents published before 2009. A critical assessment of the findings was made, not involving a formal appraisal of the data. There were few high-powered, randomized, controlled trials in this area and considerable available data was provided by retrospective studies. The Working Group recognizes this limitation. Evidence synthesis: The full text of these guidelines is available through the EAU Central Office and the EAU website (www.uroweb.org). This article comprises the abridged version of a section of the Urological Trauma guidelines. Conclusions: Updated and critically reviewed Guidelines on Urethral Trauma are presented. The aim of these guidelines is to provide support to the practicing urologist since urethral injuries carry substantial morbidity. The diversity of urethral injuries, associated injuries, the timing and availability of treatment options as well as their relative rarity contribute to the controversies in the management of urethral trauma. (C) 2010 European Association of Urology. Published by Elsevier B. V. All rights reserved.
Keywords: EAU Guidelines; Urethral trauma; Urethral injuries; Assessment; Surgical management; Delayed management; TERM-FOLLOW-UP; PRIMARY ENDOSCOPIC REALIGNMENT; BLADDER NECK CONTRACTURE; PELVIC FRACTURE; DISTRACTION DEFECTS; PROSTATOMEMBRANOUS URETHRA; POSTERIOR URETHRA; PROSTATE-CANCER; ANASTOMOTIC URETHROPLASTY; DELAYED URETHROPLASTY